Optimum Safe Hydraulic Design of Culverts - A. Al-Delewy, Abdul-Hadi; K. Al-Shukur, Abdul-Hassan; Z. M. Al-Qaisi, Atheer (Journal of Engineering and Sustainable Development, 2008)
This research aims at obtaining the "Optimum safe hydraulic design of culverts", taking into consideration the cost of excavation, bedding, material, compacted fill, hunches, protection works, and additionally involved head loss.Because of numerous shapes and materials of culverts, the wide-fame among them have been selected in this research, namely, reinforced concrete box culverts of both rectangular and squared shape, and pipe culverts of circular shape with materials of reinforced concrete, cast-iron, asbestos-cement, and ductile-steel.To be close to field conditions, discharges of (0.5, 1.0, 1.5, 2.5, 5.0, 10.0, and 15.0m3/s) have been selected to represent small, medium, and big discharges; culverts lengths of (5, 10, 15, 20, 25, 35, and 40m) have been selected to represent short, medium, and long structures. However, typical trapezoidal earthen irrigation channels have been considered to accommodate the respective culverts.To prepare the optimization model, an objective function has been formulated to cover all aforementioned costs. The optimization model involved all structural and hydraulic design constraints. The established non-linear optimization model is solved by the modified Hooke and Jeeves direct search approach. A computer program is developed to handle the aimed solution.The following categories of analyses have been considered:1. Cost as a function of discharge (for the different selected lengths).2. Cost as a function of length (for the different selected discharges).3. Number of vents as a function of discharge (for the different selected lengths).4. Number of vents as a function of length (for the different selected discharges).5. Dimensions of the culvert as a function of .....